Personalized English Language Enhancement: Teaching ESP in the Post Covid Era - Lale Fatma Yulia Ningsih (LPPM Universitas Bumigora Mataram, 2021)
COVID-19 pandemic has raised challenges for the higher education community worldwide. Of the most fundamental challenges in teaching English as a Foreign Language (EFL) during the pandemic, it is to ensure that the learning is meaningful. Online teaching and learning imply pedagogical content knowledge, mainly related to organizing and designing a better learning environment, with the help of digital technology. In this study, we provide insights into this online learning-related pedagogical content knowledge, with the goal of helping novice English language learners to navigate in this challenging time. Particularly, through a Personalised Autonomous (PA) Model approach, we conducted action research through developing a new approach to language learning and running the course during a semester in the early to mid-2020 towards 97 students. Our qualitative analysis of the samples showed that the personalized teaching model provides a unique opportunity whereby the students could address their own language learning needs to their own satisfaction which in turn stimulated their positive emotions and self-confidence. The students, however, mentioned that they experienced difficulties in finding resources and setting their personal learning goals. Finally, this research recommends that personalized learning can be a solution to distance learning during the post-pandemic era.